Narrative, Truth, and Trial - Griffin, Lisa Kern (2013)
This Article critically evaluates the relationship between constructing narratives and achieving factual accuracy at trials. The story model of adjudication— according to which jurors process testimony by organizing it into competing narratives—has gained wide acceptance in the descriptive work of social scientists and currency in the courtroom, but it has received little close attention from legal theorists. The Article begins with a discussion of the meaning of narrative and its function at trial. It argues that the story model is incomplete, and that “legal truth” emerges from a hybrid of narrative and other means of inquiry. As a result, trials contain opportunities to promote more systematic consideration of evidence. Second, the Article asserts that, to the extent the story model is descriptively correct with respect to the structure of juror decision making, it also gives rise to normative concerns about the tension between characteristic features of narrative and the truth-seeking aspirations of trial. Viewing trials through the lens of narrative theory brings sources of bias and error into focus and suggests reasons to increase the influence of analytic processes. The Article then appraises improvements in trial mechanics—from prosecutorial discovery obligations through appellate review of evidentiary errors—that might account for the influence of stories. For example, a fuller understanding of narrative exposes the false assumption within limiting instructions that any piece of evidence exists in isolation. And to better inform how adjudicators respond to stories in the courtroom, the Article argues for modifying instructions in terms of their candor, explanatory content, and timing